Studi Abrasi Pantai Padang Kota Padang Provinsi Sumatera Barat - Fajri, Ferli; ', Rifardi; Tanjung, Afrizal (Fakultas Perikanan dan Kelautan Universitas Riau, 2012)
This reseach was conducted in March to April 2012, in Padang Beach ofWest Sumatra and in Integrated Oceanology Lab of Riau University. The aim ofthis research is to reveal the progress of abration happening in Padang Beach. Themethod used in this research is the survey one. The result of this reasearch showsthat abration happened at three research stations, the abration velocity at the firststation is 0,28 m/year, the second is 0,36 m/year and at the third one is 0,12m/year. The principle causes of abration process in Padang beach are the flow andthe great wave of the sea which signed by each characteristic and the flow that thebeach abrased easily, as the bigger of wave's energy and water's flow the faster ofabration will be.